Online version of Agro-Chain greenhouse gas Emissions (ACE) calculator - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The simplified version describes only one crop (rice) and a limited number of stages of the supply chain. More elaborate version would require excessive resources; foreseen for new developments.